DINAMIKA PENERAPAN PP-71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL KASUS DI KABUPATEN GRESIK - Afiqoh, Nyimas Wardatul; Djamhuri, Ali; Purwanti, Lilik (University of Merdeka Malang, 2018)
This study aimed to comprehend the dynamics of the implementation of accrual based Government Accounting Standard in Gresik Regency by using new institutionalism perspective theory. The theory was used to analyze and comprehend the implementation of accrual based Government Accounting Standard in Management of Regional Revenue, Finance and Assets Offices by applying interpretive paradigm to comprehend the real condition happened subjectively. To describe the dynamics happened since the Government Regulation Number 71 Year 2010 was established till its implementation, processual analysis was utilized. By this mean, the researcher could formulate three important periods involved (tolerance period, trial period, and transition period). The analysis then resulted in: first of all, at the first stage the Government Regulation Number 71 Year 2010. Second, the commitment regarding the implementation of accrual based Government Accounting Standard in Gresik Regency government. Third, at the transition period in Gresik Regency government, the accrual based government accounting standard still not optimally worked.